Quality of patient-reported outcome reporting in trials of diabetes in pregnancy: A systematic review. (June 2022) - Newman, C.; Kgosidialwa, O.; Dervan, L.; Bogdanet, D.; Egan, A.M.; Biesty, L.; Devane, D.; O'Shea, P.M.; Dunne, F.P.
Abstract: Aims: Patient-reported outcomes (PROs) are reports of the patient's health status that come directly from the patient without interpretation by the clinician or anyone else. They are increasingly used in randomised controlled trials (RCTs). In this systematic review we identified RCTs conducted in women with diabetes in pregnancy which included PROs in their primary or secondary outcomes. We then evaluated the quality of PRO reporting against an internationally accepted reporting framework (Consolidated Standards of Reporting Trials (CONSORT-PRO) guidelines). Methods: We searched online databases for studies published 2013–2021 using a combination of keywords. Two authors reviewed all abstracts independently. Data on study characteristics and the quality of PRO reporting were extracted from relevant studies. We conducted a multiple regression analysis to identify factors associated with high quality reporting. Results: We identified 7122 citations. Thirty-five articles were included for review. Only 17% of RCTs included a PRO as a primary or secondary outcome. Out of a maximum score of 100 the median score was 46, indicating sub-optimal reporting. A multiple regression analysis did not reveal any factors associated with high quality reporting. Conclusions: Researchers should be mindful of the importance of PRO inclusion and reporting and include reliable PROs in trials.